A method for preparing bamboo shoot OSNC, a product made therefrom and its application

By modifying the nanocrystals of bamboo shoot head cellulose nanocrystals, bamboo shoot head OSNC was prepared, which solved the problem of limited application of bamboo shoot processing by-products in the nanofood field, and achieved high stability of modified particles in Pickering emulsion and improved curcumin transport efficiency.

CN116120470BActive Publication Date: 2025-03-28INST OF AGRI ENG TECH FUJIAN ACAD OF AGRI SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310082614.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-03-28
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize bamboo shoot processing by-products, especially insoluble cellulose contained in bamboo shoot heads, which limits its application in the field of nanofoods.

Method used

Cellulose nanocrystals (CNCs) of bamboo shoot heads were prepared by modification of octenyl succinic anhydride (OSA) to improve its surface hydrophobicity and emulsification.

Benefits of technology

The modified OSNC particles have higher thermal stability and emulsification, which can significantly improve the stability of Pickering emulsion and the transport rate of curcumin, and improve their application effect in the food functional factor emulsion transportation system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116120470B_ABST
    Figure CN116120470B_ABST
Patent Text Reader

Abstract

This invention provides a method for preparing OSNC from bamboo shoots, the resulting product, and its applications, belonging to the technical field of food functional factor emulsion transport system preparation. This invention prepares food-grade OSNC from bamboo shoots through OSA modification and applies it to the preparation of Pickering emulsions and curcumin Pickering emulsions. Results show that the modified OSNC particles exhibit a significantly increased zeta potential and a larger static contact angle, which can significantly improve the amphiphilicity and emulsifying properties of the particles. Simultaneously, the modified long-chain alkenyl chemical bonds also increase the particle strength, thereby increasing the thermal stability of the particles. Furthermore, the Pickering emulsion prepared using this OSNC has higher stability and smaller, more uniform droplet size. The curcumin Pickering emulsion prepared using this OSNC has a faster oil hydrolysis rate, which is more conducive to improving the transport rate of curcumin in the mixed micelle phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of food functional factor emulsion transport system, and in particular relates to a preparation method of bamboo shoot OSNC, a prepared product and application thereof. Background Art

[0002] my country is the world's largest producer and exporter of bamboo shoots, with an annual output of about 7 million tons of fresh bamboo shoots. As fresh bamboo shoots are easily oxidized, browned, lignified and have a short market cycle, most of the fresh bamboo shoots need further processing, except for 40% that are sold fresh. During the processing of bamboo shoots, only the tips of the bamboo shoots, which account for about 1 / 3 of the total weight, can be processed and utilized, while a large number of processing by-products such as bamboo shoots rich in dietary fiber are directly discarded due to the lack of comprehensive utilization technology, and only a few are processed into bamboo shoot powder or bamboo shoot dietary fiber. How to make full use of bamboo shoot processing by-products and improve the comprehensive utilization rate of bamboo shoots has become a technical difficulty restricting the high-quality development of the bamboo shoot industry.

[0003] With the development of nanotechnology, nanofood has become a new hot spot in the field of food processing. Nanocrystalline cellulose (CNC), as a natural polymer material, has broad application prospects in the fields of modern food and medicine due to its wide sources, low cost, biodegradability and high safety. Since bamboo shoot byproducts, such as bamboo shoots, contain a large amount of insoluble cellulose (48.3-69.78%), it is a natural raw material for the preparation of CNC. It can be used as food-grade nano solid particles to stabilize Pickering emulsions and develop bamboo shoot-derived nano health foods. At present, acid hydrolysis is the most commonly used method for preparing CNC. However, acid hydrolysis will introduce a large number of negatively charged hydroxyl groups on the surface of CNC and the surface charge strength is weak, making it show strong hydrophilicity and difficult to adsorb on the surface of hydrophobic solvents such as oils and fats, which limits the application of CNC in O / W or W / O Pickering emulsions.

[0004] Therefore, how to optimize the wettability of bamboo shoot CNC by modifying it is a key technical issue to promote its application in Pickering emulsions and further in food functional factor emulsion transport systems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing bamboo shoot OSNC, a prepared product and its application. The present invention prepares food-grade bamboo shoot OSNC by OSA modification, and applies it to the preparation of Pickering emulsion and curcumin Pickering emulsion. The results show that the Zeta potential of the modified OSNC particles is significantly increased, the static contact angle is increased, and the amphiphilicity and emulsification of the particles can be significantly improved; at the same time, the modified long-chain olefinic chemical bonds also increase the strength of the particles and increase the thermal stability of the particles; in addition, the Pickering emulsion prepared using the OSNC has higher stability and a small and uniform droplet size, and the prepared curcumin Pickering emulsion has a faster oil hydrolysis rate, which is more conducive to improving the transport rate of curcumin in the mixed micelle phase, etc.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a method for preparing cellulose nanocrystals (OSNC) modified with octenyl succinic anhydride from bamboo shoots, which specifically comprises the following steps: (1) pre-treating bamboo shoots to obtain bamboo shoot crude insoluble fiber (IDF); (2) bleaching the IDF; (3) preparing bamboo shoot nanocellulose (CNF); (4) preparing bamboo shoot cellulose nanocrystals (CNC); and (5) preparing a CNC dispersion and modifying the CNC with octenyl succinic anhydride (OSA) to obtain the OSNC.

[0008] Preferably, in step (5), the mass percentage ratio of the CNC dispersion to OSA is 1:(0.2-0.3).

[0009] Preferably, in step (5), the mass percentage ratio of the CNC dispersion to OSA is 1:0.225.

[0010] The invention also provides an OSNC prepared by the preparation method.

[0011] The present invention also provides an OSNC-Pickering emulsion prepared by using the OSNC.

[0012] Preferably, the volume fraction of the oil phase in the OSNC-Pickering emulsion is 5% to 10%, the pH value is 3.0 to 5.0, and the particle concentration of OSNC is 0.5wt% to 1.5wt%.

[0013] The wettability of solid particles is a key factor affecting the type and stability of Pickering emulsions. The concentration of solid particles significantly affects the stability of the emulsion. In addition to the concentration of solid particles, the particle size is also one of the key factors affecting the stability of Pickering emulsions. Solid particles with smaller particle sizes can be efficiently and tightly adsorbed and arranged at the oil-water interface, with a higher particle coverage rate on the droplet surface. The spatial physical barrier effect of the droplet interface is enhanced, and the prepared Pickering emulsion is more stable. Therefore, it is necessary to modify it and insert hydrophobic groups to give it amphiphilicity and adsorption capacity.

[0014] The stabilization mechanism of OSNC Pickering emulsion is as follows: 1) OSNC nanoparticles can form irreversible adsorption at the oil-water interface to reduce the oil-water interfacial tension, increase steric hindrance or electrostatic repulsion, and thus improve the stability of Pickering emulsion. 2) Reasonable emulsion formula is conducive to increasing the coverage area of ​​the oil-water interface, reducing the specific surface area of ​​the droplets, promoting the formation of a dense interface film of OSNC particles at the oil-water interface, and promoting sufficient electrostatic repulsion between the droplets to prevent the droplets from flocculating and agglomerating, thereby improving the stability of the emulsion. 3) The increase in pH enhances the hydrophobic interaction between particles, between particles and the adsorption layer on the droplet surface, and between droplets. The unadsorbed OSNC particles act as a bridge between the dispersed phase droplets, which is conducive to the formation of a three-dimensional spatial network structure of the emulsion system, preventing phase separation between droplets due to density differences, and thus improving the physical stability of the emulsion.

[0015] The present invention also provides an application of the preparation method and / or the OSNC and / or the OSNC-Pickering emulsion in a food functional factor emulsion transport system.

[0016] Preferably, the food functional factor emulsion transport system is specifically an OSNC-Pickering emulsion carrying curcumin.

[0017] Preferably, in the OSNC-Pickering emulsion carrying curcumin, the weight percentage of curcumin in the oil phase is 0.08% to 0.12%, the volume percentage of the oil phase to the water phase is (0.5 to 1.5): (9.5 to 8.5), and the mass concentration of the OSNC suspension is 1.2% to 1.8%.

[0018] Preferably, in the OSNC-Pickering emulsion carrying curcumin, the weight percentage of curcumin in the oil phase is 0.1%, the volume percentage of the oil phase to the water phase is 1:9, and the mass concentration of the OSNC suspension is 1.5%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention found that when the concentration of OSA was 2.25%, the degree of substitution of bamboo shoot CNC was 0.0286; the FTIR spectrum showed that the modified OSNC had absorption peaks of hydrophobic groups such as C=O and RCOO-; the analysis results of SEM, XRD and TGA showed that the thermal stability of the particles was improved after OSA modification, and the absolute value of the Zeta potential of OSNC was significantly increased; the contact angle of OSNC increased to 61.8°. These results all show that the surface hydrophobicity of bamboo shoot OSNC was significantly enhanced.

[0021] (2) The present invention found that the hydrophobic modification of OSA significantly reduces the surface tension of the particles and improves the emulsification of the particles. Reasonable emulsion formula (particle concentration, oil-water ratio) and system pH have a significant effect on the stability of the emulsion. The droplet size gradually decreases with the increase of particle concentration (0.5wt%~1.5wt%), and its centrifugal stability and physical stability also gradually increase; when the particle concentration is controlled at 5% and 10%, the prepared Pickering emulsion is relatively stable. At the same time, when the pH value of the emulsion is between 3.0 and 5.0, the stability of the emulsion is the highest.

[0022] (3) The embedding efficiency of the OSNC-Pickering emulsion carrying curcumin of the present invention is 82.35±1.58%, and in the simulated small intestinal digestion stage, the curcumin OSNC Pickering emulsion has a faster oil hydrolysis rate due to the smaller emulsion droplet size, which is beneficial to improve the transport of curcumin in the mixed micelle phase and further improve the bioavailability of curcumin. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 FTIR spectra of bamboo shoots CNC, MCC, OSA-MCC and OSNC in Example 1 of the present invention;

[0024] Figure 2 is the X-ray diffraction pattern in Example 1 of the present invention;

[0025] Figure 3 This is the TEM image in Example 1 of the present invention;

[0026] Figure 4 This is the CNC and particle size distribution diagram of the bamboo shoots in Example 1 of the present invention;

[0027] Figure 5 is the Zeta potential diagram in Example 1 of the present invention;

[0028] Figure 6 Schematic diagram of contact angle in Example 1 of the present invention;

[0029] Figure 7 and Figure 8This is the thermogravimetric curve of MCC and OSA-MCC and bamboo shoot CNC and OSNC in Example 5 of the present invention. DETAILED DESCRIPTION

[0030] The following examples will further illustrate the specific steps and features of the invention, which are only used for illustration and are not intended to limit the present invention. The methods used in the present invention are conventional methods in the art unless otherwise specified. The reagents and materials involved in the present invention are commercially available unless otherwise specified.

[0031] Example 1 Preparation and performance analysis of bamboo shoot OSNC

[0032] 1. The materials and reagents used are shown in Table 1, and the instruments and equipment used are shown in Table 2.

[0033] Table 1 Main experimental materials

[0034]

[0035] Table 2 Main equipment involved in the experiment

[0036]

[0037] 2. The specific preparation process is as follows:

[0038] (1) Pretreatment:

[0039] Bamboo shoots are cut from fresh green bamboo shoots as raw materials. Cut the fresh bamboo shoots into pieces and dry them in a forced air oven at 45°C for 48 hours, then grind them into powder and sieve them, mix them with ethyl acetate in a ratio of (1:4g / ml) and extract them for 1 hour, then wash them with distilled water 5 times to obtain a defatted sample. The defatted sample and distilled water in a ratio of (1:30g / ml) were stirred at a constant temperature of 80°C for 4 hours, cooled and centrifuged (4000rpm, 10min), and the residue was washed and dried with anhydrous ethanol, ground into powder and sieved through an 80-mesh sieve to obtain crude insoluble fiber (IDF).

[0040] (2) Bleaching treatment:

[0041] IDF was mixed with 5% NaOH in a proportion (mass ratio of 1:20) and stirred at 80°C for 4 hours, washed and centrifuged (4 times, 4000 rpm, 10 min), the residue was mixed with 8% H2O2 in a proportion (mass ratio of 1:20) and allowed to stand for 30 hours, washed with distilled water and centrifuged (4 times, 4000 rpm, 5 min) to remove residual H2O2.

[0042] (3) Preparation of bamboo shoot nanocellulose (CNF):

[0043] The crude fiber of bamboo shoots was degraded by secondary acid hydrolysis with low concentration acid combined with ultrasound. The conditions for the first acid hydrolysis were 5% HCl and 180W ultrasound for 90min; the conditions for the second acid hydrolysis were 10% HCl and 170W ultrasound for 60min; the reaction temperature for both acid hydrolysis was set at 45℃, and the solid-liquid ratio was 1:30g / ml. The residue after acid hydrolysis was washed with distilled water several times, adjusted to pH=7.0, and then washed with water several times, and freeze-dried to obtain CNF.

[0044] (4) Preparation of cellulose nanocrystals (CNC)

[0045] Take 3g of CNF sample, add 62wt% concentrated sulfuric acid (1:20g / ml), react at 39℃ for 45min, then add 10 times volume of distilled water to stop acid hydrolysis. Repeat centrifugation (10000rpm, 5min) to remove sulfuric acid, collect turbid supernatant, dialyze in dialysis bag (model MD7044-5m) for 6-7 days until the pH value of the solution is neutral, and obtain shoot CNC suspension, which is sealed and stored at 4℃.

[0046] (5) Preparation of OSNC by OSA modification

[0047] Accurately prepare a 2.0wt% CNC aqueous solution, stir magnetically for 5min, and then ultrasonically treat at 160W for 10min. After the solution sample is evenly dispersed in the solution, OSA is gradually added in a ratio of 1:0.225 (w / w), and the reaction temperature is controlled at 25°C. Use 0.5mol / LNaOH to adjust the pH to pH=8.50±0.1. In the esterification reaction of hydroxyl groups on the CNC or MCC skeleton with OSA, the pH is stabilized at 8.5 by continuously adding 0.5mol / LNaOH until the reaction proceeds to the point where no further addition of NaOH is required to neutralize the acidic product to ensure that all OSA has been consumed. The reaction time is 7h. After the reaction is completed, the product is neutralized to pH=7.0 with 0.5mol / LHCI to terminate the reaction. After the mixture is centrifuged (10000rpm, 10min), the precipitate is collected and washed three times with distilled water and three times with ethanol to remove the residual OSA in the precipitate. The suspension was dialyzed for 2-3 days using the above dialysis method to remove the residual ethanol, and the OSNC suspension was obtained, which was sealed and stored at 4°C for subsequent characterization analysis and preparation of Pickering emulsion. The powder sample required for subsequent testing needs to be fully crushed after the sample solution is freeze-dried.

[0048] 3. Set the contrast ratio

[0049] The bamboo shoot CNC prepared in the above process, MCC purchased from Sigma, USA, and OSA-MCC prepared from the MCC using the above method were used as comparative examples.

[0050] 4. Performance measurement

[0051] (1) Determination of degree of substitution

[0052] 20 ml of 0.1 wt% OSNC, CNC, MCC, OSA-MCC suspension (water as solvent) were measured respectively, and after magnetic stirring for 30 min, a quantitative 0.5 mol / L NaOH solution was added, and the mixture was reacted for 6 h under magnetic stirring. An appropriate amount of phenolphthalein indicator was added to the solution, and the excess NaOH in the sample was neutralized with 0.1 mol / L HCl solution. When the phenolphthalein turned red, the titration was stopped and the amount of HCl used was recorded.

[0053] The degree of substitution DS is calculated according to the following formula:

[0054]

[0055] Where 162 g / mol is the molar mass of the anhydroglucose unit (AGU), 210 g / mol is the net mass increase of the molar mass (AGU) after each acyl substitution, m is the weight of the sample, and nCOOH is the number of moles of COOH obtained by titration, which is the same as the molar amount of NaOH consumed in the titration.

[0056] (2) Fourier transform infrared spectroscopy

[0057] Before measurement, freeze-dry a certain solution sample and crush it thoroughly. Mix 10 mg of the sample with potassium bromide (1:100) and grind them together, and press them into tablets at room temperature. The measurement uses an FTIR spectrometer to scan in the mid-infrared region (400-4000cm-1), with a resolution of 4cm-1 and 64 scans. Use Origin2021 analysis software to fit and compare the absorption peaks.

[0058] (3) Crystal structure determination

[0059] The treated sample freeze-dried powder was placed in an XRD diffraction glass cell and measured using an X-ray diffractometer. A Cu target radiation source was used. The measurement was performed under the conditions of a working voltage of 30 KV and a current of 30 mA. The scanning range was 5°-70°, the scanning speed was 2°C / min, and the scanning step width was 0.02° to obtain an XRD spectrum.

[0060] (4) Scanning electron microscopy (SEM)

[0061] The sample morphology was observed using a field emission scanning electron microscope (SEM). First, the sample suspension was diluted to a certain concentration (0.001wt%), and ultrasonic homogenization was performed for 10 minutes to make the sample dispersed evenly. 10μL of the sample solution was measured and dropped onto the surface of a sterile and clean mica sheet using a pipette, dried at room temperature and pressure, and then observed using a SEM.

[0062] (5) Particle size and potential analysis

[0063] First, the sample solution was diluted to 0.02wt%. The particle size and Zeta potential of the sample were measured using a Malvern nanoparticle sizer. The test conditions were set as follows: temperature 25°C, scattering index 1.47, and each sample was tested three times. The results were expressed as the average value. The samples were all ultrasonically treated (10min, 160W) before the particle size was measured.

[0064] (6) Contact angle measurement

[0065] The three-phase contact angle of the powder sample was measured at 25°C using a contact angle analyzer. The powder sample was made into a flat disc with a diameter of 13 mm and a thickness of 2 mm, placed in an optical glass tube containing soybean oil, and a drop of ultrapure water (constant 5 μL) was deposited on the surface of the disc using a high-precision syringe. The image after the droplet equilibrium was recorded using a camera, and the sample contact angle was analyzed using software. Each sample was measured in parallel 3 times.

[0066] (7) Thermal stability determination

[0067] The thermal stability of the samples was determined using a thermogravimetric analyzer. The mass change of the samples was measured in a nitrogen atmosphere at a constant heating rate of 10°C / min in the range of 30-790°C, and the samples were kept at 790°C for 5 min.

[0068] 4. Results Analysis

[0069] The results of the degree of substitution of OSNC and OSA-MCC are shown in Table 3. The FTIR spectra of CNC, MCC, OSA-MCC and OSNC are shown in Table 3. Figure 1 The X-ray diffraction pattern is shown in Figure 2 As shown in the TEM image Figure 3 As shown, the CNC and particle size distribution of bamboo shoots are shown in Figure 4 The Zeta potential diagram is shown in Figure 5 As shown, the contact angle is Figure 6 The thermogravimetric curves of MCC and OSA-MCC and bamboo shoot CNC and OSNC are shown in Figure 7 , Figure 8 shown.

[0070] Table 3 Analysis of substitution degree of OSNC and OSA-MCC

[0071]

[0072] Note: Different lowercase letters indicate significant differences between samples

[0073] The results show that when the concentration of OSA is 2.25%, the degree of substitution of the bamboo shoot CNC is 0.0286; the FTIR spectrum shows that the modified OSNC has absorption peaks of hydrophobic groups such as C=O and RCOO-; SEM, XRD and TGA analysis results show that the thermal stability of the particles is improved after OSA modification, and the absolute value of the Zeta potential of OSNC is significantly increased; the contact angle of OSNC increases to 61.8°. These results all show that the surface hydrophobicity of bamboo shoot OSNC is significantly enhanced.

[0074] Example 2 Preparation and Performance Analysis of OSNC-Pickering Emulsion

[0075] 1. The materials and reagents used are shown in Table 4, and the instruments and equipment used are shown in Table 5.

[0076] Table 4 Main experimental materials

[0077]

[0078] Table 5 Main equipment involved in the experiment

[0079]

[0080] 2. The specific preparation process is as follows:

[0081] The OSNC prepared in Example 1 was used as a particle stabilizer, and soybean oil was used as the oil phase. The Pickering emulsion was prepared by emulsification with high-speed shear homogenization. The oil-water volume ratio was 0.05:0.95, and the preparation process was as follows: a certain amount of 1.0wt% OSNC suspension was measured, and the pH of the suspension was adjusted to 7.0 with 0.25mol HCL, and the system oil phase volume fraction was 5% at 160w microwave ultrasound for 10min. A certain amount of soybean oil was pipetted with a pipette gun and added to the sample suspension, and a high-speed shear homogenizer was used to homogenize at a speed of 12000rpm for 2min, and the mixture was repeated 3 times to obtain an OSNC-Pickering emulsion.

[0082] 3. Performance measurement

[0083] The dynamic hanging drop method was used to measure the interfacial tension (σ) of bamboo shoot CNC and OSNC suspensions of different concentrations adsorbed on the soybean oil-water interface as a function of adsorption time (t). The droplets were analyzed using SCA20 software, and the interfacial tension σ of the sample solution was calculated based on the Young-Laplace equation.

[0084] The volume fraction of the oil phase was controlled to be 5%, the pH of the OSNC suspension was adjusted to 7.0 with 0.25 mol HCL, and OSNC suspensions with particle concentrations of 0.5 wt%, 0.8 wt%, 1.0 wt%, and 1.5 wt% were prepared respectively, a certain amount of soybean oil was added, and a high-speed shear homogenizer was used to homogenize at a speed of 12000 rpm for 3 min to prepare OSNC Pickering emulsions with different particle concentrations;

[0085] The particle concentration of OSNC suspension was fixed at 1.5wt%, the pH of the suspension was adjusted to 7.0 with 0.25mol HCL, microwave ultrasound was applied at 160w for 10min to make the agglomerated OSNC dispersed evenly, soybean oil was added at a ratio of 5%, 10%, 20% and 30% of the oil phase volume fraction (Φ), and OSNC Pickering emulsions with different Φ emulsion formulas were obtained by homogenizing with a high-speed shear homogenizer at a speed of 12000rpm for 3min;

[0086] Under the conditions of OSNC particle concentration of 1.5wt%, pH=7.0, and system oil phase volume fraction of 5%, the OSNC suspension was ultrasonically homogenized for 10min, and a high-speed shear was used to homogenize at a speed of 12000rpm for 3min to prepare a Pickering emulsion. 10ml of the prepared emulsion was respectively added to a test tube, and the pH was adjusted to 3.0, 5.0, and 7.0 with 0.5mol HCL. After being stored at low temperature for a period of time, it was used for subsequent measurements;

[0087] After the above freshly prepared Pickering emulsion is diluted in a certain proportion, the particle size distribution and volume average particle size of the emulsion particle size sample are measured using a Zeta nanoparticle size potentiometer, wherein the relative refractive index of the emulsion is set to 1.095, the dispersant is ultrapure water, the refractive index of the aqueous phase is 1.33, and each sample is measured three times to take the average value; the microstructure and emulsion particle size of the Pickering emulsion are observed by laser confocal microscopy (CLSM). The CISM analysis of all emulsion samples was carried out at room temperature. Before observation, a mixed dye containing 0.1wt% Nile red (for oil phase staining) and 0.1wt% Nile blue (for OSNC staining) was prepared, and 30μL of the mixed dye was added to 100μL of fresh emulsion for staining for 30min. Take 10μL of the dyed emulsion and drop it on a glass slide, immediately cover it with a coverslip, and then observe it according to the CLSM method. The excitation wavelength of Nile red is set to 488nm, and the excitation wavelength of Nile blue is 633nm, and the image is collected in high-resolution mode;

[0088] With reference to the determination method of Gross-Rother et al., 420 μL of fresh emulsion prepared by different methods was taken into a centrifuge tube, and the sample stability was analyzed by the German LUM full-function stability analyzer (LUMiSizer), with the centrifugal speed set to 1500 rpm / min, the centrifugal time set to 50 min, the contour line set to 50, and the temperature set to 25 ° C. According to the principle of centrifugal separation analysis and optical near-infrared detection, the transmission spectra of different samples were obtained;

[0089] 8 ml of the freshly prepared emulsion was transferred into a 10 ml sample bottle, which was sealed and stored in a refrigerator at 4°C. The emulsion stability was observed on the 0th day, the 7th day, and the 30th day, and the appearance of the emulsion was recorded with a camera.

[0090] 4. Results Analysis

[0091] The results show that: the present invention found that the hydrophobic modification of OSA significantly reduces the surface tension of the particles and improves the emulsification of the particles. Reasonable emulsion formula (particle concentration, oil-water ratio) and system pH value have a significant effect on the stability of the emulsion. The droplet size gradually decreases with the increase of particle concentration (0.5wt%~1.5wt%), and its centrifugal stability and physical stability also gradually increase; when the particle concentration is controlled at 5% and 10%, the prepared Pickering emulsion is relatively stable. At the same time, when the pH value of the emulsion is between 3.0 and 5.0, the stability of the emulsion is the highest.

[0092] Example 3 Preparation and performance analysis of OSNC-Pickering emulsion loaded with curcumin

[0093] 1. The materials and reagents used are shown in Table 6, and the instruments and equipment used are shown in Table 7.

[0094] Table 6 Main experimental materials

[0095]

[0096] Table 7 Main equipment involved in the experiment

[0097]

[0098] 2. The specific preparation process is as follows:

[0099] 0.1% (w / w) curcumin was dissolved in soybean oil as the oil phase, and magnetic stirring was performed at 45°C for 30 minutes to ensure that curcumin was completely dissolved in the soybean oil; 1.5% (w / w) OSNC suspension was accurately prepared using the method in Example 2, the pH was adjusted to 7.0, and ultrasonication was performed for 10 minutes to mix it evenly. The oil phase and the aqueous phase were mixed in a volume ratio of 1:9, and homogenized at 12000rpm for 2 minutes using a high-speed shearing machine, and repeated 3 times to obtain an OSNC emulsion delivery system embedded with curcumin. Ensure that the entire preparation process should be carried out under light-proof conditions, and the container used should be wrapped in tin foil to prevent curcumin from decomposing during the preparation process. The prepared emulsion was stored at room temperature.

[0100] 3. Performance measurement

[0101] Take 2 mL of the prepared sample emulsion, add 8 mL of dichloromethane, vortex for 30 seconds, centrifuge at 10,000 rpm and 4°C for 5 minutes, take the lower layer of liquid and measure the ultraviolet absorbance of the emulsion sample at 425 nm; and calculate the free curcumin content in the emulsion according to the turmeric standard curve;

[0102] Take 7.5mL of curcumin emulsion samples of different concentrations and mix them with 2.5mL of ultrapure water, and prepare 10mL of SGF (containing 3.2mg / mL pepsin, 0.2M NaCl solution, and 6.5mL / L concentrated hydrochloric acid), and then add the curcumin emulsion to SGF. Adjust the pH value of the solution to 2.0 with 0.5M hydrochloric acid, control the system temperature to be stable at 37°C, and stir at 100rpm for 1h to simulate gastric digestion. Take samples at fixed points at 20, 40, and 60min for subsequent research and analysis;

[0103] After gastric digestion is completed, the digestion sample is taken out immediately. Prepare 20mL of SIF (containing 1mg / mL pancreatic juice, 15mg / mL bile salts, 10mM CaCl2, pH=7.0) and add it to the sample that has completed gastric digestion. Use 0.5M sodium hydroxide solution to adjust the pH to 7, control the system temperature to 37°C, and stir slowly at 100rpm for 2h to simulate intestinal digestion. During intestinal digestion, use 0.1M NaOH to stabilize the pH value of the digestive fluid at 7.0±0.1, and record the amount of NaOH added. Take samples at fixed points at 30, 60, 90 and 120min for subsequent analysis;

[0104] Using a Malvern particle size analyzer, the droplet size (D[4,3]) of the original emulsion sample, the emulsion sample after SGF digestion (20, 40, 60 min), and the emulsion sample after SIF digestion (30, 60, 90, 120 min) was measured by dynamic light scattering (DLS). 100 μL of each sample was diluted to a certain concentration to reduce the multiple scattering effect. The relative refractive index of the emulsion was set to 1.10 (calculated from the refractive index of soybean oil of 1.47 and the refractive index of the water phase of 1.33), and the sample particle size and particle size distribution were analyzed using a Malvern particle size analyzer;

[0105] The Zeta potential of the original emulsion and the digested sample was tested using the above instrument. The sample was diluted 100 times with 0.01M phosphate buffer and its Zeta potential value was measured at room temperature in a potential sample cell;

[0106] Take 1.0mL of the original emulsion sample, the sample after SGF digestion for 20, 40, and 60min, and the sample after SIF digestion for 30, 60, 90, and 120min, respectively, add 20μL of 0.1wt% Nile red solution (for oil phase staining) and 0.1wt% Nile blue (for CNC staining), mix well, take 10μL of the emulsion and place it on a clean glass slide, cover it with a cover glass, and use CLSM to observe the microstructure of all emulsion samples. Set the excitation light of Nile red to 488nm, the argon laser of Nile blue to 633nm, and use Zen digital image processing software to acquire and process images;

[0107] Collect the samples digested by the gastrointestinal tract, centrifuge them at 10000rpm and 4℃ for 20min, and obtain three separated phases, of which the upper layer is the undigested oil layer, the middle is the micelle layer and the lower precipitate. After high-speed centrifugation, the middle micelle layer contains dissolved curcumin. Collect the middle micelle layer in a centrifuge tube and filter it with a 0.22μm filter membrane to remove the undissolved curcumin crystals. Prepare a mixed extract of methanol: n-hexane = 2:3, add it to the above filtered sample, vortex and shake for 20s to mix thoroughly, centrifuge at 10000rpm and 4℃ for 5min to separate the organic phase, collect the light yellow clear liquid layer in a 10mL test tube, repeat the above steps and extract twice to ensure that curcumin can be completely extracted. Dilute the extract with an appropriate amount of ethanol and measure its absorbance at 425nm, and then calculate the concentration of digested curcumin according to the curcumin standard curve;

[0108] The bioavailability of curcumin in the emulsion was calculated according to the following formula:

[0109] The concentration of curcumin in the micelles was determined according to the above method, and the retention rate was calculated according to the following formula:

[0110] 4. Results Analysis

[0111] The results showed that the embedding efficiency of the OSNC-Pickering emulsion carrying curcumin of the present invention was 82.35±1.58%, and in the simulated small intestinal digestion stage, the curcumin OSNC Pickering emulsion had a faster oil hydrolysis rate due to the smaller particle size of the emulsion droplets, which was beneficial to improve the transport of curcumin in the mixed micelle phase and further improve the bioavailability of curcumin.

[0112] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. Application of OSNC-Pickering emulsion in food functional factor emulsion transport system, characterized in that: The volume fraction of the oil phase in the OSNC-Pickering emulsion is 5% to 10%, the pH value is 3.0 to 5.0, and the particle concentration of OSNC is 0.5 wt% to 1.5 wt%; the preparation method of OSNC comprises the following steps: (1) Pretreatment of bamboo shoots to obtain crude insoluble fiber (IDF); (2) IDF bleaching treatment; (3) Preparation of shoot nanocellulose CNF; (4) Preparation of bamboo shoot cellulose nanocrystals CNC; (5) preparing a CNC dispersion and modifying it with octenyl succinic anhydride (OSA) to obtain the OSNC; The modification method is as follows: OSA is added in a weight ratio of 1:0.225 to a uniformly dispersed 2.0 wt% CNC aqueous solution, the temperature is controlled at 25°C, and 0.5 mol / L NaOH is used to adjust the pH to 8.50±0.

1. The reaction time is 7 h. After the reaction is completed, the product is neutralized to pH=7.0 with 0.5 mol / L HCI, and then precipitated, washed, dialyzed, freeze-dried, and crushed to obtain the OSNC.

2. The use according to claim 1, characterized in that: The food functional factor emulsion transport system is specifically an OSNC-Pickering emulsion carrying curcumin.

3. The use according to claim 2, characterized in that: In the OSNC-Pickering emulsion carrying curcumin, the weight percentage of curcumin in the oil phase is 0.08% to 0.12%.

4. The use according to claim 3, characterized in that: In the OSNC-Pickering emulsion carrying curcumin, the weight percentage of curcumin in the oil phase is 0.1%, and the volume percentage of the oil phase to the water phase is 1:9.

Citation Information

Patent Citations

  • Surface modified cellulose nanocrystalline and preparation method and application thereof

    CN106892984A